VD_FINDINFO AI 231/12 - 352/2012 vom 29. Oktober 2012 - VD Tribunal cantonal (2012)
RADIATION DU RÔLE, DÉCISION D'IRRECEVABILITÉ, MOTIVATION DE LA DEMANDE | 61 let. b LPGA, 27 al. 5 LPA-VD, 79 al. 1 LPA-VD